1980
DOI: 10.1097/00000658-198008000-00016
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Oral versus Parenteral Preoperative Metronidazole on Sepsis Following Colon Surgery

Abstract: The incidence of wound infection following surgery on the colon is reduced by the preoperative adminstration of appropriate antibiotics. Quantitative bacteriologic studies raise the fundamental question as to whether effective antibiotic prophylaxis results from reduction of the bacterial content of the gut prior to surgery or whether effective tissue levels of the antibiotic is the key factor. Oral neomycin and metronidazole have been shown to markedly reduce the incidence of wound infection following colon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…This amount of time was considered more than adequate on the basis of studies in humans, which revealed the bacteroides content of fecal flora was reestablished by 6 days after cessation of orally administered metronidazole. 19 To determine that bacteria had recolonized the duodenum in the cats of our study, samples of duodenal fluid were submitted for bacterial culture. Blood samples also were obtained and analyzed for serum concentrations of total protein, albumin, cobalamin, and folate.…”
Section: Methodsmentioning
confidence: 99%
“…This amount of time was considered more than adequate on the basis of studies in humans, which revealed the bacteroides content of fecal flora was reestablished by 6 days after cessation of orally administered metronidazole. 19 To determine that bacteria had recolonized the duodenum in the cats of our study, samples of duodenal fluid were submitted for bacterial culture. Blood samples also were obtained and analyzed for serum concentrations of total protein, albumin, cobalamin, and folate.…”
Section: Methodsmentioning
confidence: 99%
“…The most common combinations include an aminoglycoside (neomycin and, less often, kanamycin, which is only available in injectable form in the United States) plus a medication with anaerobic activity, usually erythromycin [427][428][429][430][431][432][433][434] or metronidazole. 432,433,[435][436][437][438][439] In placebo-controlled studies, the oral combination was significantly more effective than placebo in reducing SSIs. 427,433,434,439,440 Postoperative SSI rates were 0-11% with neomycin plus erythromycin 427-432 and 2-13% with neomycin and metronidazole.…”
Section: Efficacymentioning
confidence: 99%
“…427,433,434,439,440 Postoperative SSI rates were 0-11% with neomycin plus erythromycin 427-432 and 2-13% with neomycin and metronidazole. [436][437][438] Combinations of neomycin and tetracycline, 440 neomycin and clindamycin, 436 and neomycin and tinidazole 441 have also been used successfully, with postoperative SSI rates of <10%. The use of metronidazole as a single agent appears to be less effective, with reported SSI rates of 12-15%.…”
Section: Efficacymentioning
confidence: 99%
“…A variety of oral agents administered after MBP have been evaluated (Table 4). The most common combinations include an aminoglycoside (neomycin and, less often, kanamycin) plus a medication with activity against anaerobes, usually erythromycin [16,91] or metronidazole [92][93][94].…”
Section: Current Trends In Sap and Infection Preventionmentioning
confidence: 99%